Impact of Individual Viral Gene Segments from Influenza A/H5N8 Virus on the Protective Efficacy of Inactivated Subtype-Specific Influenza Vaccine - Moatasim, Yassmin (Pathogens, 2021)
Since its emergence in 2014, the highly pathogenic avian influenza H5N8 virus has continuously and rapidly spread worldwide in the poultry sector resulting in huge economic losses. A typical inactivated H5N8 vaccine is prepared using the six internal genes from A/PR8/1934 (H1N1) and the two major antigenic proteins (HA and NA) from the circulating H5N8 strain with the HA modified to a low pathogenic form (PR8(HA/NA-H5N8)). The contribution of the other internal proteins from H5N8, either individually or in combination, to the overall protective efficacy of PR8-based H5N8 vaccine has not been investigated. Using reverse genetics, a set of PR8-based vaccines expressing the individual proteins from an H5N8 strain were rescued and compared to the parent PR8 and low pathogenic H5N8 strains and the commonly used PR8(HA/NA-H5N8). Except for the PR8-based vaccine strains expressing the HA of H5N8, none of the rescued combinations could efficiently elicit virus-neutralizing antibodies. Compared to PR8, the non-HA viral proteins provided some protection to infected chickens six days post infection. We assume that this late protection was related to cell-based immunity rather than antibody-mediated immunity. This may explain the slight advantage of using full low pathogenic H5N8 instead of PR8(HA/NA-H5N8) to improve protection by both the innate and the humoral arms of the immune system.